2021
DOI: 10.1002/hep4.1729
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Model for a Drug Assessment of Cytochrome P450 Family 3 Subfamily A Member 4 Substrates Using Human Induced Pluripotent Stem Cells and Genome Editing Technology

Abstract: In drug development, a system for predicting drug metabolism and drug‐induced toxicity is necessary to ensure drug safety. Cytochrome P450 family 3 subfamily A member 4 (CYP3A4) is an important drug‐metabolizing enzyme expressed in the liver and small intestine, and predicting CYP3A4‐mediated drug metabolism and drug‐induced toxicity is essential. We previously developed procedures to differentiate human induced pluripotent stem (iPS) cells into hepatocyte‐like cells (HLCs) or intestinal epithelial‐like cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…More recently, using the same technology, the group generated a CYP3A4-KO iPSC line, and from which generated HLCs to evaluate CYP3A4-mediated drug metabolism and drug-induced toxicity. Using a small group of model drugs, including acetaminophen, amiodarone, desipramine, leflunomide, tacrine, and tolcapone, the authors confirmed that the CYP3A4-KO HLCs were able to correctly predict CYP3A4-mediated toxicity (Deguchi et al, 2021).…”
Section: Hlcs Derived From Ipscs Genome-edited With Crispr/cas9mentioning
confidence: 82%
See 1 more Smart Citation
“…More recently, using the same technology, the group generated a CYP3A4-KO iPSC line, and from which generated HLCs to evaluate CYP3A4-mediated drug metabolism and drug-induced toxicity. Using a small group of model drugs, including acetaminophen, amiodarone, desipramine, leflunomide, tacrine, and tolcapone, the authors confirmed that the CYP3A4-KO HLCs were able to correctly predict CYP3A4-mediated toxicity (Deguchi et al, 2021).…”
Section: Hlcs Derived From Ipscs Genome-edited With Crispr/cas9mentioning
confidence: 82%
“…With the CRISPR/Cas9 system, isogenic cell lines with desired mutations could be generated for a variety of biomedical applications. In several studies that appeared in the last few years, iPSCs were modified by CRISPR/Cas9 and the genetically modified cells were further differentiated into HLCs for toxicity applications (Takayama et al, 2018;Deguchi et al, 2019;Kim et al, 2020;Deguchi et al, 2021). Using the CRISPR/Cas9 system, a CYP3A4-NeoR-EGFP transgenic reporter human iPSC line was established by inserting a neomycin resistant gene (NeoR) and an enhanced green fluorescent protein (EGFP) into the CYP3A4 locus (Takayama et al, 2018).…”
Section: Hlcs Derived From Ipscs Genome-edited With Crispr/cas9mentioning
confidence: 99%
“…Human iPS cells derived from individuals with single nucleotide polymorphisms (SNPs) in cytochrome P450 (CYP) 2D6 recapitulated the poor metabolizer phenotype by differentiation into HLCs [ 4 ]. In addition, genome editing technology successfully recapitulated the phenotypes of poor metabolizers in HLCs and revealed the contribution of specific CYP enzymes in pharmacokinetics [ 5 , 6 ]. Moreover, hepatocyte transplantation technologies using HLCs sheets [ 7 ], spheroids [ 8 ], and organoids [ 9 ] have been developed as an alternative to living donor liver transplantation.…”
Section: Introductionmentioning
confidence: 99%